2007
DOI: 10.1002/macp.200600614
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Isothermal and Nonisothermal Epoxy‐Amine Cures by Model‐Free Isoconversional Methods

Abstract: Model‐free and model‐fitting kinetic approaches were applied to isothermal and nonisothermal DSC data on epoxy cure. The dependence of the effective activation energy on the extent of cure was determined using integral and differential isoconversional methods. A different shape of the dependence in the kinetically controlled regime (α < 0.4) was found when compared to the dependence typically reported for epoxy‐amine systems. This result was shown to arise from the presence of low amounts of bisphenol A in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…By applying Eq. (5), to the studied systems, an apparent activation energy E a of 56.59 kJ/mol has been found for the epoxy-amine system (E_TETA), which is consistent with typical results (50-70 kJ/mol) for a number of epoxy-amine polymerizations [51][52][53][54][55]. For the epoxy-DES systems the values of apparent activation energy are much higher, between 86.26 and 99.77 kJ/mol, as expected since in the systems the curing agent is not present, confirming the calorimetric results reported in Table 4.…”
Section: Kinetic Modeling Of Nonisothermal Reactionssupporting
confidence: 87%
“…By applying Eq. (5), to the studied systems, an apparent activation energy E a of 56.59 kJ/mol has been found for the epoxy-amine system (E_TETA), which is consistent with typical results (50-70 kJ/mol) for a number of epoxy-amine polymerizations [51][52][53][54][55]. For the epoxy-DES systems the values of apparent activation energy are much higher, between 86.26 and 99.77 kJ/mol, as expected since in the systems the curing agent is not present, confirming the calorimetric results reported in Table 4.…”
Section: Kinetic Modeling Of Nonisothermal Reactionssupporting
confidence: 87%
“…However, it is noteworthy that the E α varies in a narrower range (about 10 kJ/mol) with respect to α compared to the range reported for other epoxy-amine systems [34]. Values around 50 kJ/mol were obtained, which are in good agreement with Kissinger and Ozawa model-fitting kinetics values and literature data for the autocatalytic reaction of an epoxy–amine system [35]. The rate-determining steps for autocatalytic reactions correspond to the formation of a trimolecular transition state amine–epoxy–hydroxyl, maybe as shown in Figure 8, where HX represents a hydrogen-bond donor.…”
Section: Resultssupporting
confidence: 80%
“…It decreased gradually up to 30 kJ/mol due to the autocatalytic mechanism [ 60 , 61 , 62 ], as shown in Figure 3 a. Several studies have reported the same trends for the activation energy [ 62 , 63 , 64 ]. On the other hand, for cured DKL and DOL with DDM, the activation energy in the initial stage (α value from 0 to 0.8) slightly climbed, and after that it quickly increased in the later stage due to the self-curing reaction pathway ( Figure 3 a).…”
Section: Lignin-based Resinsmentioning
confidence: 79%